PHOTOPROTECTIVE EFFECT OF SUNSCREEN CREAM WITH ADDITION OF CARRAGEENAN AND BLACK MANGROVE FRUIT (Rhizopora mucronata Lamk.) - Sri Purwaningsih; Ella Salamah; M. Nur Adnin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
The need of people’s face protection from sun exposure is continuosly increasing. However, the available sunscreen in the market are mostly chemicaly generated. Seaweed (Kappaphycus alvarezii) produced carrageenan, which can be used as stabilizer, thickener, and emulsifier on sunscreen production. Black mangrove fruit (R. mucronata) contains an antioxidant activity, tanin, flavonoids, and phenolic compounds, which are potential to be used for UV light absorber as well as skin protector. The aims of this research were to determine: (1) the best carrageenan concentration in the cream; (2) content of total phenol, flavonoids, and tannin of mangrove fruit extract; and (3) Sun Protection Factor (SPF) value of sunscreen cream. The experiment used a complete random design and with Duncan test. The result showed that the best natural sunscreen formulation was an addition of 0.5% carrageenan and 1% extract from R. mucronata. The best characteristics of natural sunscreen were found within the level of 7.62 pH, 38.250 cP viscosity, 100% emulsion stability, 3.72% shrinkage, and <102 colonies/g total microbial, 10.21 ± 0.06 SPF content, 37.90% total phenol, 0.51% total flavonoids, and 6.20 mg/g tannins. Keywords: antioxidant, carrageenan, flavonoids, Rhizophora mucronata, SPF